(untitled) (Papeles, 2014)
This article is the result of a research in Bogotá to a group of teachers, in order to understand the perceptions they have on the skills strengthening around creative thinking using Problem Based Learning (PBL, ABP in Spanish). The method used was qualitative, with an exploratory scope and also a phenomenological design. The results indicated that teachers perceive the PBL as a strategy that promotes significant learning and encourages the formation of students, which is because it becomes an ally to strengthen skills especially the creative ones.